9514 1404 393
Answer:
Step-by-step explanation:
To factor the quadratic expression Ax² +Bx +C, you look for factors of the product AC that have a sum of B.
AC = 10(-3) = -30 = 1(-30) = 2(-15) = 3(-10) = 5(-6)
These factor pairs have sums of -29, -13, -7, -1. The pair we want is (3)(-10), which has a sum of -7.
Using this pair of factors, we can rewrite the "B" term as a sum.
10x² -7x -3 = 10x² +3x -10x -3
This can be factored by grouping pairs of terms together:
= (10x² +3x) +(-10x -3)
= x(10x +3) -1(10x +3)
= (x -1)(10x +3)
If we consider the length to be greater than the width, then these binomial factors might represent ...
length: (10x +3)
width: (x -1)